Evidence and Persistence of Education Inequality in an Early-Tracking System: The German Case - Annabelle Krause; Simone Schüller (Institute for the Study of Labor (IZA), 2014)
This article reviews empirical evidence on the early tracking system in Germany and the educational inequalities associated with it. Overall, the literature confirms the existence of considerable social, ethnic, gender- and age-related inequalities in secondary school track placement. Studies on tracking timing and track allocation mechanisms reveal that postponement of the selection decision and binding teacher recommendations may reduce certain (mainly social) inequalities. Furthermore, recent evidence concerning long-term consequences of tracking on labor market outcomes suggests that sizeable built-in flexibilities in the German system succeed in compensating for initial (age-related) education inequalities. The paper concludes with an outline and discussion of the most promising pathways for future research in order to help design inequality-reducing policy recommendations.
Keywords: I24; I28; J24; 330; educational inequality; tracking; school system; Germany